Water footprint assessment of water supply treatment process : a case study of semambu water treatment plant - Nurul Asyikin, Mohd Rofi (2016)
In many parts of the world, freshwater is already a scarce and overexploited, raising the concern about global water scarcity. Previously, the Life Cycle Assessment (LCA) has been used to assess the impact of pollution to the environment. In 2002, Water Footprint Assessment (WFA) has been introduced. However, WFA has been only conducted to assess the product. In this study, the sustainability assessment by using WFA approach was conducted to assess the water supply treatment process (WSTP) of Semambu Water Treatment Plant. The study identified the type of water footprint (WF) at each stage of WSTP and calculated its water footprint for the period 2010 to 2015. Two factors that influenced the accounting of WF such as population and monsoonal changes were also evaluated. From the results obtained, the increasing water due to the increases population and land use factors affected the total water footprint per year; however the pattern of rainfall intensity due to monsoonal changes did not directly influenced the total amount of water footprint however it has slightly affected the total water intake. Thus, if the pattern keeps increasing due to the unregulated development and occurrences of climate changing, the water intake river is afraid to be insufficient and this may lead to water scarcity. The findings suggest interventions to reduce the water footprint will likely have as great impact on freshwater resources availability by regulating the placement area of development.